Influencia de la densidad de siembra y enmiendas de pH en el crecimiento y rendimiento de quinua (Chenopodium quinoa) variedad Tunkahuan en la Estación Argelia, Loja - Sanmartín Sanmartín, Zoila María (2023)
Quinoa is the main crop in the Andes. Its nutritional value play a crucial role to the ideal balance of amino acids, which is an excellent component in diets. The objective of this research was to analyze the influence of planting density and pH amendments on the growth and yield of Chenopodium quinoa variety Tunkahuan. It was at La Argelia Station, using three planting densities: 200,000 plants/ha (0.10 m 0.5 m), 133,333 plants/ha (0.15m*0.5m) and 66,666 plants/ha (0.30m*0.5m) and amendments; dolomite and humic acids, under a completely randomized block design (DBCA), three replicates. The height and vegetation cover were taken every 20 days, the phenology with the BBCH scale, the biomass was recorded in six states, the pH was measured three times during the crop cycle, the quantification of chlorophyll was in anthesis and beginning of filling of grain, the length of the panicle at physiological maturity. The number of grains per plant, per m², weight, yield and harvest index were measured at the end of the trial. The results suggest that the higher the density, the higher the biomass and height values. Likewise, the application of humic acids favored the height and the pH of the soil. The plants subjected to the dolomite treatment at higher density showed higher chlorophyll values, with the use of humic acids a high panicle length was obtained, the highest number and weight of grains was found with dolomite, the highest number of grains per m² it was obtained at higher densities, with the application of humic acids a higher yield and harvest index was obtained. This study helps quinoa producers to implement new production technologies in terms of density and liming. Words keys: Chenopodium quinoa, growth, liming, maturity physiological.